STRATEGI PENGEMBAGAN JIWA KEAGAMAAN PADA TAHAP-TAHAP PERTUMBUHAN ANAK - Muh. Sudirman; Mustaring Mustaring (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2020)
This article is an analysis from a psychological point of view about the development of religious souls at the stages of child growth. The stages of the child's mental development will change periodically along with the physical growth and spiritual development. To preserve the soul so as not to be polluted from negative influences, such as harassment and violation of religious values ​​and humanitarianism. So it is very necessary for the formation of educators and parents of the child's soul. From the results of the assessment obtained that understanding; 1). Basically, the Islamic education of each individual or child in their development is greatly influenced by innate factors (heredity), environmental factors (family, school and community), and supernatural factors; 2). Every child in the development of a religious soul that is accepted and felt at each stage of their growth experiences certain influences, therefore the strategy for developing a religious soul in children must be adjusted to the stages of their growth.